(3GbJUGOjGJ GdfbhO h GdJehjd GdOhdjs - (3LhRja(B, (3OGfjGdRs; (3OjajO aGfghR(B, s ((3GdQjGV(B:s (3OGQ GdeQjN(B,s, 2010)
(3GdJhGUd eY GdYGde GdeJZjQ (B.. (3JOabGJ GdJLGQI h JOabGJ QCS GdeGd h ejRGf GdeOahYGJ , Shb GdUQa GdCLfHj h fXe SYQ GdUQa Hjf GdeGVj h GdMGVQ , GdCOhGJ GdeGdjI GdOhdjI h GdCShGb h GdeDSSGJ (B: (3GdShb GdBLdI ddYedI h GdeQGLYI GdeGdjI GdOhdjI , YhGFO GdaGFOI h eNGWQ SYQ GdaGFOI h eTJbGJ GdChQGb GdeGdjI , GdeUGQa GdOhdjI h GdeUGQa GdeQcRjI h GdeDSSGJ GdYdjG dUfY GdSjGSGJ GdJehjdjI , GdHfjGf GdeGdj GdOhdj h GdGbJUGOjGJ GdUGYOI , JMOjO SYQ GdUQa h ejRGf GdeOahYGJ (B: (3GdefGgL GdJbdjOjI dJMOjO ejRGf GdeOahYGJ , GdefgL GdfbOj h efgL GdeMaXI GdeGdjI dejRGf GdeOahYGJ h JMOjO SYQ GdUQa , GWGQ GdGbJUGO GdeaJhM Ydi GdYGde GdNGQLj , GdSjGSI GdGbJUGOjI aj Xd CSYGQ GdUQa GdKGHJI , eSJhi GdCSYGQ h GdfGJL GdMbjbj h UfY GdSjGSI GdGbJUGOjI , UfY GdSjGSI Ydi GdeSJhi GdeMdj h eJYOO GdLfSjI aj GdShb GdYGdejI (B: (3UfY GdSjGSI GdGbJUGOjI GdeMdjI aj Xd GbJUGO GdYhdeI , JfSjb GdSjGSGJ h GdGJMGO GdfbOj h GdefGWb GdeSJgOaI (B.s
Keywords: (3GdEbJUGOs; (3GdJehjd GdOhdjs; (3GdfbhOs